1959
DOI: 10.1029/jz064i012p02239
|View full text |Cite
|
Sign up to set email alerts
|

Hydromagnetic theory of geomagnetic storms

Abstract: A hydromagnetic theory is presented which explains the average characteristics of geomagnetic storms. The magnetic storm is caused by a sudden increase in the intensity of the solar wind. Stresses are then set up in the geomagnetic field by the solar plasma impinging upon the geomagnetic field and becoming trapped in it. These stresses, which are propagated to the earth as hydromagnetic waves, account for the observed average magnetic storm variations. The sudden commencement of the magnetic storm is due to a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
477
0
1

Year Published

1976
1976
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 768 publications
(491 citation statements)
references
References 22 publications
6
477
0
1
Order By: Relevance
“…We estimate Dst from the calculated electron and proton energy content with the Dessler-Parker-Sckopke (DPS) relation [Dessler and Parker, 1959;Sckopke, 1966] and the sum of the estimated Dst is reasonable comparing with the observed Dst. Ring current electrons in this study may contribute 7.5% as much energy content as ring current protons over the L range.…”
Section: Discussionmentioning
confidence: 68%
“…We estimate Dst from the calculated electron and proton energy content with the Dessler-Parker-Sckopke (DPS) relation [Dessler and Parker, 1959;Sckopke, 1966] and the sum of the estimated Dst is reasonable comparing with the observed Dst. Ring current electrons in this study may contribute 7.5% as much energy content as ring current protons over the L range.…”
Section: Discussionmentioning
confidence: 68%
“…Combining with the Dessler-Parker-Sckopke relationship [Dessler and Parker, 1959;Sckopke, 1966], we have…”
Section: Results From 20 Idealized Stormsmentioning
confidence: 99%
“…Geomagnetic storms are identified using the Dst or SYM-H indices, whose depression is mainly attributed to the enhanced ring current in the inner magnetosphere [Dessler and Parker, 1959;Frank, 1967]. The major source of the ring current is regarded as the plasma transported from the main plasma sheet.…”
Section: Introductionmentioning
confidence: 99%
“…The modern concept of a radiation belt of bouncing and drifting protons and electrons trapped within the magnetosphere and producing the ring current was proposed by Singer (1957) and confirmed with the discovery of the radiation belts by both US and Soviet teams in 1959 (Van Allen and Frank, 1959b;Van Allen et al, 1959a;Vernov et al, 1969). Shortly thereafter Dessler and Parker (1959) and Sckopke (1966) showed that the magnetic field depression at the center of the Earth was proportional to the energy content of the particles trapped in the magnetic field. The depression on the surface of the Earth, the equatorial average value of which we term the D st index, is additionally enhanced by currents within the Earth that exclude the field of the newly-formed ring current from the Earth's interior.…”
Section: Introductionmentioning
confidence: 89%